Transcriptional down-regulation of the Wnt antagonist SFRP1 in haematopoietic cells of patients with different risk types of MDS - Reins, Jana; Mossner, Maximilian; Neumann, Martin; Platzbecker, Uwe; Schumann, Christiane; Thiel, Eckhard; Hofmann, Wolf-Karsten (Leukemia research, 2010)
Secreted frizzled related protein 1 (SFRP1) is an extracellular antagonist of the Wnt signalling pathway that plays an important role in the pathogenesis of solid tumours and haematopoietic malignancies. SFRP1 has been observed to be transcriptionally down-regulated due to hypermethylation in acute and chronic leukaemia, but so far not in myelodysplastic syndrome (MDS). Moreover, it has been shown that the epigenetic inactivation of SFRP1 correlates with an overexpression of the Wnt receptor Frizzled 3 (Fzd3) in acute leukaemia. Using real-time quantitative reverse transcription polymerase chain reaction (RT-PCR) we examined mRNA expression of SFRP1 and Fzd3 in bone marrow cells derived from 121 patients with different risk types of MDS, acute myeloid leukaemia (AML) and acute lymphoblastic leukaemia (ALL). We employed pyrosequencing to quantify promoter DNA methylation in MDS and acute leukaemia. We detected significant lower mRNA transcription of SFRP1 in MDS compared to healthy individuals. However, DNA sequence mutations or frequent elevated DNA methylation levels of the SFRP1 promoter could not be observed in MDS but in AML and ALL as previously reported. The expression levels of Fzd3 were up-regulated in both acute leukaemia and MDS. Our data show a significant transcriptional down-regulation of SFRP1 as a common event in AML, ALL and - as demonstrated for the first time - in MDS. An inactivation of SFRP1 and the transcriptional up-regulation of Fzd3 seem to be associated with an activation of the Wnt signalling pathway in these haematopoietic diseases.
Gesehen am 12.05.2023